Using Technology Acceptance Model to Evaluate the Utilization of Kolintang Instruments Application - Wikarsa, Liza; Angdresey, Apriandy (Jurnal Pekommas, 2021)
To preserve traditional Kolintang musical instruments, originating from Minahasa (North Sulawesi, Indonesia), Aplikasi Musik Kolintang was developed and can be run on web browsers and Android-based smartphones with several controllers to attract users’ attention. This study aims to explore the acceptability and utilization of this application, especially the use of a webcam as a sensor for motion detections, and identify the modifications to make for better user experiences. Technology Acceptance Model (TAM) was adopted to determine user acceptance and behavioral intentions toward the application. The TAM variables used in this study were perceived usefulness, perceived ease of use, attitude towards usage, and behavioral intentions. External variables were also included, namely application design, application design, and expectancy. An online questionnaires-based survey was conducted to collect data from 177 people randomly selected at Universitas Katolik De La Salle Manado. The results suggested that all variables in the proposed framework either directly or indirectly have effects on the overall behavioral intention to use the application as they have statistically significant positive correlations. The respondent propensity to embrace and use the application was high leading to an increase in positive attitude toward usage, which consequently influenced the behavioral intention to use. Several modifications were indeed required to improve the quality of the application and enrich the user experience.